(untitled) (Advances in Applied Mathematics and Mechanics, 2025)
In this article, we study a parabolic equation with both nonlinear time-derivative term and nonlinear diffusion term by the finite volume element method. The optimal error estimate in H^1-norm is proved for fully discrete scheme. The suboptimal error estimate in L^2-norm is proved both for semi-discrete scheme and fully discrete scheme. We prove the existence of solution for the fully discrete scheme. Numerical results show the effectiveness of our method.